RESPON SISWA TERHADAP PENGGUNAAN MEDIA KOMIK DALAM PEMBELAJARAN IPA MATERI LISTRIK STATIS SISTEM DARING - Erawati, Fera; Munirotuzzakiyah, Munirotuzzakiyah; Haqiqi, Arghob Khofya (Universitas Esa Unggul, 2021)
This study aims to determine the response of students to the use of comic media in science learning with static electricity material which the authors expect to get a positive response from students and can help reduce student boredom in science learning using comic media. By making media that is fun and does not make students bored, students will be more enthusiastic in learning and the learning process can take place well without any complaints from students who feel bored by only using written media. Material static electricity is one of the branches of physics material that is important for students to understand. By using comic book media in delivering static electricity with a few pictures, it can reduce student boredom and it will be more fun than just writing. This research method uses a qualitative method by surveying the opinions of several students in different schools regarding the use of comic media on online system static electricity material using the whats app group. The results of the study showed that many students were interested in the use of comic media compared to only using writing in science learning with static electricity in online systems. Keywords: student responses, comic media, science learning, static electricity, online